Ethics and experience : moral theory from just war to abortion - Steffen, Lloyd H., 1951- (Rowman & Littlefield Publishers, 2012)
Ethics and Experience introduces students to the key topics in moral theory through provocative moral issues-just war, abortion, physician assisted suicide, the death penalty and more. Steffen helps students bridge the gap between ethical theory and experience through developing a "common agreement" ethical system that is applicable to a variety of moral problems and issues with clear language and real-life examples